PERSEPSI PEREMPUAN MENGENAI FENOMENA POLITIK DALAM PEMILIHAN KEPALA DESA NGADAS KABUPATEN MALANG - Syakira SyafiqyaTsabita Putri Hartono; Muchammad Miqdad; Syahara Bhatari Alamsyah; Sri Zul Chairiyah (LPPM Universitas Ekasakti Padang, 2023)
Women's perception and participation in political phenomena in Indonesia still needs to be encouraged, bearing in mind the patriarchal culture which has an impact on the minimal role of women in politics and as citizens. Elections are a means of participating in politics by becoming voters or participants. Elections are a tool for everyone, including women. The smallest unit of election organizers is the village. One of the villages with a unique political phenomenon is Ngadas Village in Malang Regency, where the village head also plays the role of customary head. However, what is interesting is the role and views of women on all the political dynamics that occur in Ngadas Village. Using descriptive qualitative methods, the research will examine in depth the perceptions and roles of women in Ngadas Village regarding the political phenomena that occur. Interview and observation techniques were used to collect data and obtain information through related documentation or literature. The results of the study show that the perceptions and roles of women in Ngadas Village tend to be passive in selecting village heads. Participation is carried out only as a form of handing over voting rights to give legitimacy to those in power.